ANALISIS KETERLAKSANAAN IMPLEMENTASI KURIKULUM 2013 DI KELAS 4 SD SE-KABUPATEN MAGETAN - Dewi Tryanasari; Edy Riyanto (Jurnal Penelitian LPPM (Lembaga Penelitian dan Pengabdian kepada Masyarakat) IKIP PGRI MADIUN, 2014)
The curriculuminIndonesiahas beenamended several times, most recently in 2013.One of thedistrictsusedfortestingisMagetaninvolving11elemetary schools. The purpose of this researches to describe curriculum 2013 implementation of enforceability forfourth gradewholeMagetan. This research used aphenomenological approachtoqualitative research. theSubjects usedto teacher fourth gradeat theelementary school that used curriculum 2013. The object researchesthatexploredisthelearning, the learningprocess, andevaluationinstrumentsdeveloped bythe teacher. The collecting data techniqueincludesdocumentation, observationandinterviews. Researchersact asthe ma i n i n s t r ume n t i n c o l l e c t i n g d a t a a n d a d d i t i o n a l i n s t r ume n t f o rm offieldnotesandchecklist.The results showedthat: (1) theimplementation of thecurriculum 2013 for fourth gradeinMagetannot fully yet implementedin terms oflearning plan  development, learning implementation, andevaluation. This is happend becausethe mindsetsof the teacher not complete yetchange. and thecommunity of society isn't involve yet in this case; and(2) the main obstaclein learning isimplementation about scientificapproachis not good yet, thatrequire studentstoinquirybasedprocess throughandcarefully plannedbythe teacher.